Marine and urban influences on summertime PM2.5 aerosol in the Po basin using mobile measurements. (November 2015) - Wolf, R.; El Haddad, I.; Crippa, M.; Decesari, S.; Slowik, J.G.; Poulain, L.; Gilardoni, S.; Rinaldi, M.; Carbone, S.; Canonaco, F.; Huang, R.-J.; Baltensperger, U.; et al.
Abstract: We report ambient measurements using a high-resolution time-of-flight aerosol mass spectrometer (HR-ToF-AMS) on a mobile platform in the southeast Po Valley (Italy) in summer 2012. During the PEGASOS southbound campaign measurements of non-refractory aerosol were performed in urban and rural environments as well as near the coast of the Adriatic Sea. Organic source apportionment analysis of the aerosol mass spectrometer data was carried out using positive matrix factorization and multilinear engine (ME-2) receptor modelling. Five major organic aerosol components were identified: hydrocarbon-like organic aerosol (HOA), semi-volatile oxygenated organic aerosol (SVOOA), low volatility oxygenated organic aerosol (LVOOA), cooking organic aerosol (COA) and a regionally influenced highly oxygenated organic aerosol (HOOA). Essential changes in both aerosol composition and concentration were induced by the ventilation and recirculation of air masses in the East-West direction of the valley (land/sea breeze system) and via the Apennine mountain range (mountain/valley wind system). An urban increment of the non-refractory aerosol mass concentration in Bologna of about 1.6–2.3 μg/m 3 compared to the surrounding regions was quantified which can be explained by the sum of local contributions from cooking activities and from hydrocarbon-like aerosol related to traffic emissions. Highlights: Mobile AMS measurements were conducted in the southeast Po Valley. Aerosol composition and sources similar within the Po Valley plume. Minor influence from marine source areas during the campaign. Urban aerosol increment in Bologna explained by traffic and cooking processes.